Analysis of Heavy Metals Pb and Mn in River Water at Putri Cempo Landfill - Matin, Hashfi Hawali Abdul; Setyono, Prabang; Dzihni, Asfi; Adiningsih, Aulia Rahmatya; Agustina, Aulia Tsalatsa; Rahmadhani, Sakina Enova; Al-Dzahabi, Muhammad Adib; Kencanawardhani, Larasati Gumilang (Universitas Diponegoro, 2025)
Waste is a crucial issue with far-reaching impacts on the environment, public health, and economy. The Putri Cempo landfill receives waste from Surakarta City. Waste can pollute the river near the landfill, given the location of the river that adjoins and is close to residential areas. The purpose of this research was to analyze the river water quality around the Putri Cempo landfill for heavy metals Pb and Mn. The research was conducted by taking samples directly from the river and then analyzing the heavy metal content. The results were compared with river water quality standards according to Indonesian Government Regulation 22/2021. The results showed that the Pb content in river was -0.02392344 mg/L and Mn was 4.206021703 mg/L. From these results, the Pb content in the river did not exceed the quality standard limit, whereas the Mn content exceeded the quality standard limit. It can be concluded that the river water around Putri Cempo landfill has been contaminated with Mn. Heavy metals in high levels can harm living things and the environment, can cause death to aquatic biota and plants, disease in humans, degrade water quality and damage river aesthetics. Further evaluation of stakeholders is required to address heavy metal pollution